Assessing Pb and Cd levels in the water of Kapuas River of Central Kalimantan using water hyacinth as a biomonitor plant - Olfa, Maria; Santoso, Heri Budi; Rakmawati, Rakmawati; Mintowati, Evi Kuntorini (Journal of Degraded and Mining Lands Management, 2025)
This study evaluated heavy metal pollution in the Kapuas River, Central Kalimantan, with a focus on lead (Pb) and cadmium (Cd). This study focused on the Kapuas River due to the high anthropogenic activities that cause pollution and the lack of previous biomonitoring studies. Water and water hyacinth (Eichhornia crassipes) samples were collected from four locations in Kapuas Regency between March and April 2023 using a purposive sampling method. This study aimed to evaluate the levels of Pb and Cd in water bodies and the roots of water hyacinth in the Kapuas River. The results showed that the Pb concentration in river water averaged 0.00184-0.00451 mg/L, and Cd in river water averaged 0.00182-0.02595 mg/L, indicating that the river water has been contaminated with Pb and Cd but still within the quality standard. The Pb concentration in water hyacinth roots averaged 4.98-7.33 mg/kg, while the Cd concentration was <0.001 mg/kg. The pollution index of the Kapuas River ranged from 2.29 to 3.08, classified as lightly polluted. The correlation between Pb in the roots of water hyacinth and the water was between -0.60 and -0.89, indicating that the lower the Pb in the water, the higher the Pb in the roots of water hyacinth. Therefore, water hyacinth has the potential to be a bioindicator of Pb pollution.